The Predictive Role of Tooth Extractions, Oral Infections, and hs-C-Reactive Protein for Mortality in Individuals with and without Diabetes: A Prospective Cohort Study of a 12 1/2-Year Follow-Up - Lise Lund Håheim; Kjersti S. Rønningen; Morten Enersen; Ingar Olsen (Journal of Diabetes Research)
The predictive role of high-sensitivity C-reactive protein (hs-CRP), number of tooth extractions, and oral infections for mortality in people with and without diabetes is unclear. This prospective cohort study is a 12 1/2-year follow-up of the Oslo II study, a health survey in 2000. In all, 12,764 men were invited. Health information was retrieved from 6434 elderly men through questionnaire information, serum measurements, and anthropometric and blood pressure measurements. Diabetes was reported by 425 men. Distinct differences were observed in baseline characteristics in individuals with and without diabetes. In the diabetes group, age and hs-CRP were statistically significant whereas in the nondiabetes group, age, hs-CRP, number of tooth extractions, tooth extractions for infections and oral infections combined, nonfasting glucose, systolic blood pressure, total cholesterol, regular alcohol drinking, daily smoking, and level of education were independent risk factors. The number of tooth extractions <5 was inversely related whereas more extractions increased the risk. Multivariate analyses showed that hs-CRP was a significant predictor in persons with diabetes and tooth extractions and oral infections combined; the number of teeth extracted and hs-CRP were for persons without diabetes. Infection and inflammation were associated with mortality in individuals both with and without diabetes.